Physical environment increase the transmission of tuberculosis - Deni Metri (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The physical environment is a contributing factor to tuberculosis cases in several developing countries. Indonesia ranks third in the world for tuberculosis cases. According to the World Health Organization (WHO) the increase in cases was attributed to problems with sanitation and poor living conditions. The appropriate method to prevent transmission is to interrupt transmission from three factors: the host, the agent, and the environment to children. The source of tuberculosis (TB) transmission in children is adult patients with smear-positive TB. Purpose: To prevent transmission of pulmonary TB to children, which is related to the physical environment. Method: A descriptive correlational, specially focusing on cross-sectional method. The study took place from August 2025 in Community Health Center, Kotabumi. The independent variable was physical environment, meanwhile the dependent variable included tuberculosis transmission. Using random sampling and slovin formula 38 respondents were selected who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using chi square test and multivariate with logistic regression. Results: Analysis multivariate shows that home lighting and home cleanliness are significantly associated with TB prevention, with OR 8.370 (p = 0.001) and OR 4.825 (p = 0.016). Ventilation (OR 2.091; p = 0.238) and air humidity (OR 2.959; p = 0.060) did not show a significant relationship. Conclusion: Home lighting and home cleanliness was identified as the most influential factor in preventing pulmonary TB transmission.